SOUL searching: a theoretical framework for change initiation and institutional transformation for Indian higher education institutions. (11th October 2022) - Gupta, Ankur; Sawhney, Sahil
The Indian higher education sector is at an inflection point. Declining student enrolments, non-conformance to quality standards and industry disconnect have raised serious existential concerns for a large number of institutions. Therefore, there is an urgent need for institutions to transform themselves to create value and successfully navigate the challenges confronting them. We present strategy, operations, urgency, leadership (SOUL), a comprehensive theoretical framework for institutional transformation, customised for Indian academia, enabling leadership teams to introduce validated interventions and global best-practices at their institutions in a phased manner. SOUL is novel, relevant and timely, especially in the Indian context considering that disruption and crisis create opportunities for initiating change and undertaking institutional transformation.